Development of BRS-Pontal beans growing with treated domestic wastewater in protected environment - Raimundo Gomes Filho; Silvaneide Silva; Clayton Carvalho; Gregorio Faccioli; Tatiana Nunes; Simone Feitosa; Leonaria Carvalho (International Journal of Recycling of Organic Waste in Agriculture)
Purpose To evaluate the development of beans (Phaseolus vulgaris L.), variety of BRS Pontal, in protected environment, irrigated with different irrigation levels due to crop evapotranspiration (ETc) and concentrations of treated domestic wastewater. Method The experiment was carried out in a protected environment using an experimental design arranged in randomized blocks with a 3 x 4 factorial scheme, in which the bean crop was submitted to different concentrations of 0, 50 and 100% of the treated domestic wastewater and four irrigation levels corresponding to 50%, 75%, 100% and 125% of crop evapotranspiration and four replications. The data to estimate crop evapotranspiration using the FAO 56 Penman-Monteith method were obtained from a meteorological station installed inside the protected environment. Results The irrigation levels and the interaction with the concentrations of treated domestic wastewater significantly influenced the stem diameter, height and number of bean leaves at a level of 1%, while the concentrations did not significantly influence the number of leaves. Conclusion The treated domestic wastewater contained enough nutrients to meet the nutritional needs of the bean crop in relation to the treatment that received only water from the supply system. The use of treated domestic wastewater may constitute an alternative to save quality water in the growing of bean.